Penguatan Strategi Pemasaran Rawat Jalan Eksekutif Rumah Sakit Melalui Penyelenggaraan Webinar DCG Indonesia di LMS Plataransehat Kemenkes - Anandito Birowo; Tri Lestari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
The increasingly competitive health care industry requires hospitals to strengthen executive outpatient services through targeted marketing strategies and capacity building. As a training institution accredited by the Ministry of Health, DCG Indonesia organized a free webinar entitled “Marketing Strategies for Executive Outpatient Services in Hospitals” to fulfill accreditation requirements and support continuing education. This article describes the planning, implementation, and outcomes of the two-hour webinar, which used lectures, discussions, and question–answer sessions and was integrated with the Plataransehat LMS for pre-test, post-test, and evaluation. Of 60 targeted participants, 29 (48%) completed the full learning sequence. The mean knowledge score increased from 60.69 to 75.17 (a gain of about 24%), while overall participant satisfaction reached 93.76%, with very good ratings for instructors, materials, and event management. The webinar was effective in enhancing knowledge and providing practical guidance for hospitals in designing comprehensive, context-sensitive, and evidence-based marketing strategies for executive outpatient services.